The Use of Metaverse in Higher Education: The Future of Collaborative Learning - Ifan Sadewa; Ridwan; Karomah Alif Sabilla Rustam Sutoto (Siber Nusantara of Education and Sport Review, 2024)
The emergence of the Metaverse has revolutionized the field of education, providing new avenues for collaborative and immersive learning. This paper explores the application of Metaverse technology in higher education, emphasizing its potential to transform traditional pedagogical approaches. By offering a virtual environment where students can interact with both peers and educators in real-time, the Metaverse supports more interactive and engaging learning experiences. The study aims to identify how the Metaverse can enhance collaborative learning and the challenges associated with its integration. A qualitative research method was employed, gathering data from case studies and expert interviews. The results suggest that while the Metaverse offers significant advantages in terms of student engagement and global access, there are technological and financial challenges that institutions must overcome. The conclusion emphasizes the need for strategic planning and resource allocation to fully integrate the Metaverse into higher education.